2016
DOI: 10.1016/j.bbrep.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A relation between osteoclastogenesis inhibition and membrane-type estrogen receptor GPR30

Abstract: Disruption of the cooperative balance between osteoblasts and osteoclasts causes various bone disorders, some of which are because of abnormal osteoclast recruitment. Osteoporosis, one of the bone disorders, is not effectively treated by currently available medicines. In addition to the development of novel drugs for palliative treatment, the exploitation of novel compounds for preventive treatment is important in an aging society. Quercetin, a major flavonoid found in many fruits and vegetables, has been expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…3). Recent advances have shed light on the mechanisms of osteoclast 9,76,86,87 and chondrocyte 88–92 differentiation and function; however, how GPCR signaling regulates osteoclasts and chondrocytes remains largely unknown. The expression of multiple GPCRs by different bone cells and the activation of multiple signaling pathways by a single GPCR, together with the wide variety of GPCRs and the signaling redundancy often seen downstream of GPCR activation, pose significant challenges to clarifying a given GPCR’s function in bone development and disease.…”
Section: Signaling Backgroundmentioning
confidence: 99%
“…3). Recent advances have shed light on the mechanisms of osteoclast 9,76,86,87 and chondrocyte 88–92 differentiation and function; however, how GPCR signaling regulates osteoclasts and chondrocytes remains largely unknown. The expression of multiple GPCRs by different bone cells and the activation of multiple signaling pathways by a single GPCR, together with the wide variety of GPCRs and the signaling redundancy often seen downstream of GPCR activation, pose significant challenges to clarifying a given GPCR’s function in bone development and disease.…”
Section: Signaling Backgroundmentioning
confidence: 99%
“…36,37 Several studies illustrated that quercetin suppressed the phosphorylation of Akt and affected nuclear factor kappa B (NF-kB), AP-1 and NFATc1 to inhibit osteoclast differentiation. 38,39 Activation of NF-kB signaling pathway by RANKL, TNF-a or IL-1 can induce osteoclast differentiation to extend osteoclast survival and increase bone resorption. 40 Genistein directly suppressed osteoclastic differentiation induced by TNF-a and suppressed the expression of two transcription factors c-Fos and NFATc1 caused by NF-kB up regulation to inhibit bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…53 Similarly, our results confirmed that GPR30 could be activated by rutin. Although the G15 used in this experiment is a highly specific antagonist with no affinity for other receptors of estrogen, 54 the specific binding mode of rutin to GPR30 needs further study in the future. Besides, to further develop the understanding of the underlying mechanisms, more researches are also necessary.…”
Section: Discussionmentioning
confidence: 99%